2014
DOI: 10.15653/tpg-140473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endometrial echotexture and cervical cytology in cows during and after treatment of endometritis

Abstract: Echotexture parameters determined by the evaluation of sonographic B-mode images reflect changes in the endometrium and could be used for the evaluation of the recovery period after treatment of endometritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Clinically, cytology examination is restricted in practice to confirm uterine inflammation, and histopathology is usually considered the more accurate method to detect, define and classify endometritis [ 4 ]. However, cytological examination was also recommended to diagnose endometritis and monitor the elimination of inflammatory cells after treatment in cows [ 14 ] and mares [ 7 ]. In addition, the expression features of pro-inflammatory cytokines may serve as a further confirmation of clinical infection, but the examination on endometrial biopsy samples harms the reproductive system in cattle [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, cytology examination is restricted in practice to confirm uterine inflammation, and histopathology is usually considered the more accurate method to detect, define and classify endometritis [ 4 ]. However, cytological examination was also recommended to diagnose endometritis and monitor the elimination of inflammatory cells after treatment in cows [ 14 ] and mares [ 7 ]. In addition, the expression features of pro-inflammatory cytokines may serve as a further confirmation of clinical infection, but the examination on endometrial biopsy samples harms the reproductive system in cattle [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few techniques are applied in the diagnosis of endometritis in cattle and mare, including hematology, bacteriology, vaginoscopy, ultrasonography, transrectal palpation, cytology and histological examination [ 22 ], while in commercial sheep and goat flocks, diagnosis of endometritis is usually done by inspection of the pelvic region and vaginal examination using vaginal scope [ 12 ]. Several studies reported that cervical cytology was used for the diagnosis of endometritis in cows due to advantages, such as easy procedure, short time reporting and simple equipment [ 14 , 29 ], while other diagnosis methods including vaginoscopy, ultrasonography, cytokines detection and histopathology were characterized by a long results waiting time and the need of special tools. In addition, some researchers examined the transcripts or serum levels of inflammatory cytokines, and APPs reflect the systemic immune status as diagnostic indicators of subclinical endometritis [ 11 ].…”
mentioning
confidence: 99%
“…However, although the treatment methods mentioned above are generally used in the treatment of clinical endometritis, there is no generally accepted treatment method for subclinical cytologic endometritis ( 44 ). As an alternative therapy for antibiotic infusion in endometritis, a wide range of chemical agents including hyperimmune serum ( 1 ), autologous plasma, E. coli lipopolysaccharides ( 47 ), pre-acetic acid containing drugs ( 26 ), and irritant solutions containing antiseptics ( 33 ), or antioxidants ( 28 ) are proposed.…”
Section: Introductionmentioning
confidence: 99%